Estrategias metodológicas activas para mejorar la ortografía en los estudiantes de sexto grado, paralelo b, de la escuela Alonso de Mercadillo del cantón Loja, período académico 2017-2018 - Mejia Molina, Diana Yazmin (2018)
The research project “Active methodology strategies to improve the spelling of sixth grade students in class B at the Alonso de Mercadillo school in the canton of Loja, academic year 2017-2018” has as its general objective to improve spelling through the application of active methodology strategies so that the sixth grade students in class B at the Alonso de Mercadillo General Basic Education school in the city of Loja during the 2017-2018 academic year write correctly. The type of study was descriptive, and the methods used were descriptive, observational, analytical, synthetic, inductive, deductive and hermeneutic. The technique was a survey and the instrument a questionnaire. The procedure consisted of theoretical foundation, diagnosis, workshop design, application and evaluation. The results were an improvement in spelling for the 33 students of sixth grade class B. The conclusion is that by implementing workshops with active methodology strategies in basic education spelling is improved significantly.